Characterization of the complete chloroplast genome of the medicinal herb Eleutherococcus nodiflorus and its phylogenetic implications. Issue 11 (2nd November 2022) - Li, Minjun; Gong, Qiuyi; Zhou, Manjia; Liu, Qiang; Cheng, Rubin
Abstract: Eleutherococcus nodiflorus (Dunn) S. Y. Hu is a momentous medicinal plant belonging to the Araliaceae family. In the current investigation, we determined the complete chloroplast genome of E. nodiflorus and analyzed the phylogenetic relationship among Eleutherococcus plants. The chloroplast genome of E. nodiflorus exhibited a typical quadripartite structure with a full length of 156, 770 bp, including 133 genes, containing 88 protein-coding genes, 8 rRNA genes, 37 tRNA genes, and 1 presumed pseudogene ( ycf1 ). The overall GC content observed was 37.95%, with the highest GC content of 43.02% found in the IR region. Comparative genome analysis revealed five highly variable regions among Eleutherococcus species, providing potential markers for further investigations on species identification and population genetics. A total of 44 small simple repeats were identified throughout the chloroplast genome of E. nodiflorus . The phylogenetic analysis indicated a sister relationship between E. nodiflorus and E. eleutheristylus, suggesting a close genetic relationship between the two Eleutherococcus plants. These results enhance the understanding of the plant evolution within Eleutherococcus plants and provide basic genetic resources for the development of species identification and investigation of population genetic diversity of the Eleutherococcus genus and Araliaceae.